14-17 yaş arası sporcularda antrenör-sporcu ilişkisi kalitesinin ahlaki karar alma ve saldırgan davranışları belirlemedeki rolü - Demirci, Saygın (My University, 2020)
Amaç: Bu çalışmanın amacı 14-17 yaş arası sporcularda antrenör-sporcu ilişkisi kalitesinin ahlaki karar alma tutumlarını ve saldırgan davranışları belirlemedeki rolünü ve bu değişkenlerin cinsiyet, spor türü, spor deneyimi ve antrenörle çalışma süresine göre değişip değişmediğini incelemektir.Gereç ve Yöntem: Çalışmaya 229 erkek (X̄yaş = 15.24 ± 1.03) ve 54 kız (X̄yaş = 15.83 ± 1.02) olmak üzere toplam 283 sporcu katılmıştır. Katılımcılara kişisel bilgi formu ile birlikte, Antrenör- Sporcu İlişkisi Envanteri, Altyapı Sporlarında Ahlaki Karar Alma Tutumları Ölçeği-2 ve Buss-Perry Saldırganlık Ölçeği uygulanmıştır. Verilerin analizinde çoklu hiyerarşik regresyon ve bağımsız örneklerde t testi kullanılmıştır. Bulgular: Yapılan analiz sonuçlarına göre, antrenör-sporcu ilişkisinin bağlılık alt boyutunun ahlaki karar alma tutumlarının hileyi benimseme alt boyutunun olumlu yordayıcısı, yakınlık alt boyutunun ise hileyi benimsemenin olumsuz yordayıcısı olduğu, ayrıca bağlılık alt boyutunun saldırganlığın sözel saldırganlık, öfke, fiziksel saldırganlık alt boyutlarının ve genel saldırganlığın negatif yordayıcısı olduğu görülmüştür (p<0.05). Bununla birlikte antrenör-sporcu ilişkisi kalitesi ve saldırganlıkta spor deneyimi ve antrenörle çalışma süresine göre anlamlı olarak farklılıklar olduğu bulunmuştur (p< 0.05). Sonuç: Elde edilen sonuçlar, antrenör-sporcu ilişkisi kalitesinin altyapı sporcularında ahlaki karar alma tutumlarını ve saldırganlığı etkilediğini, ayrıca spor deneyimi ve antrenörle çalışma süresinin de antrenör-sporcu ilişkisini ve saldırganlığı etkilediğini göstermektedir.

Purpose: The aim of this study is to examine the role of coach-athlete relationship quality in determining attitudes to moral decision-making and aggressive behaviors in athletes aged between 14-17 and whether these variables vary according to gender, type of sport, sports experience and duration of training with the coach.Materials and Method: 229 boys (X̄age = 15.24 ± 1.03) and 54 girls (X̄age = 15.83 ± 1.02) in total of 283 athletes participated in the study, Along with the personal information form, The Coach-Athlete Relationship Questionnaire, The Attitudes to Moral Decision Making in Youth Sport Questionnaire-2 and the Buss-Perry Aggression Questionnaire were administered to the participants. Multiple hierarchical regression and independent samples t-tests were used for the analysis of the data.Results: According to the results of the analysis, commitment dimension of coach-athlete relationship is found as the positive predictor and closeness dimension is found as the negative predictor of acceptance of cheating dimension of attitudes to moral decision making in youth sport; also commitment dimension of coach-athlete relationship is found as the negative predictor of verbal aggression, anger, physical aggression and aggression in general (p<0.05). It has been found that there are significant differences in coach-athlete relationship according to the sports experience and the duration of working with the coach, and the aggressiveness differs significantly according to the sports experience and the time of working with the coach similarly (p <0.05).Conclusion: The results show that the quality of the coach-athlete relationship effects moral decision-making attitudes in youth sport and aggression in the athletes, as well as the sports experience and the duration of working with the coach have an impact on the coach-athlete relationship and aggression.
Keywords: aggression; ahlaki karar alma; altyapı sporları; Antrenör-sporcu ilişkisi; Coach-athlete relationship; moral decision making; Öğrenim ve öğretim; saldırganlık; Spor; Sports; Study and teaching; youth sports